In silico study of pseudoprogression in glioblastoma: collaboration of radiologists and radiation oncologists in the estimation of extent of high dose RT region - Belanova, Renata; Sprlakova-Pukova, Andrea; Standara, Michal; Janu, Eva; Koukalova, Renata; Kristek, Jan; Burkon, Petr; Kolouskova, Ivana; Prochazka, Tomas; Pospisil, Petr; Chakravarti, Arnab; Slampa, Pavel; et al. (Biomedical papers, 2020)
Background and Aim. Oncologists play a vital role in the interpretation of radiographic results in glioblastoma patients. Molecular pathology and information on radiation treatment protocols among others are all important for accurate interpretation of radiology images. One important issue that may arise in interpreting such images is the phenomenon of tumor "pseudoprogression"; oncologists need to be able to distinguish this effect from true disease progression.Exact knowledge about the location of high-dose radiotherapy region is needed for valid determination of pseudoprogression according to RANO (Response Assessment in Neuro-Oncology) criteria in neurooncology. The aim of the present study was to evaluate the radiologists' understanding of a radiotherapy high-dose region in routine clinical practice since radiation oncologists do not always report 3-dimensional isodoses when ordering follow up imaging. Methods: Eight glioblastoma patients who underwent postresection radiotherapy were included in this study. Four radiologists worked with their pre-radiotherapy planning MR, however, they were blinded to RT target volumes which were defined by radiation oncologists according to current guidelines. The aim was to draw target volume for high dose RT fields (that is the region, where they would consider that there may be a pseudoprogression in future MRI scans). Many different indices describing structure differences were analyzed in comparison with original per-protocol RT target volumes. Results: The median volume for RT high dose field was 277 ccm (range 218 to 401 ccm) as defined per protocol by radiation oncologist and 87 ccm (range 32-338) as defined by radiologists (median difference of paired difference 31%, range 15-112%). The Median Dice index of similarity was 0.46 (range 0.14 - 0.78), the median Hausdorff distance 25 mm. Conclusion: Continuing effort to improve education on specific procedures in RT and in radiology as well as automatic tools for exporting RT targets is needed in order to increase specificity and sensitivity in response evaluation.
Keywords: pseudoprogression; RANO; glioblastoma; radiotherapy; high-dose field